Book Reviews (comm, 2006)
Abstract Nihoul, P. and Rodford, P. (2004). EU electronic communications law. Competition and regulation in the European telecommunications market. New York: Oxford University Press. ISBN 0-19-926340-X (802 pp.) (Eric Van Heesvelde) Von Feilitzen, C. (Ed.). (2004). Young people, soap operas and reality TV. Yearbook 2004. Göteborg University: Nordicom. ISBN 91-89471-28-8 (255 pp.) (Jelle Mast) Kelly-Holmes, H. (2005). Advertising as multilingual communication. New York: Palgrave MacMillan. ISBN 1-4039-1725-6 (hardcover) (206 pp.) (Jos Hornikx) Born, G. (2004). Uncertain vision. Birt, Dyke and the reinvention of the BBC. London: Secker and Warburg/Random House. ISBN: 0436205629 (564 pp.) (Leen d'Haenens)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4uMjAwNi4wMTU